Female-Only Classes in a Rural Context: Self-Concept, Achievement, and Discourse - Hope E. Wilson; Jeanie Gresham; Michelle Williams; Claudia Whitley; Jimmy Partin (Journal of Research in Rural Education, 2013)
Two middle schools in rural east Texas implemented an optional, single-sex program. Although previous studies have documented the effects of single-sex instruction, and recent educational innovations have focused on its benefits, little research has investigated its effects in rural contexts. This study found that for rural populations, patterns of discourse differ between female-only and coeducational classes, with all-female classes participating in higher levels of thinking and engaging in more discourse overall. However, girls in single-sex classes had significantly lower levels of general self-concept than girls in coeducational classes. There were no statistically significant differences in the achievement test scores between the groups. This research indicated that findings from urban contexts may not be generalizable to rural populations.